SOCIAL MEDIA’S EFFECT ON YOUTH PARTICIPATION IN MALAYSIA’S GENERAL ELECTION 15th. - Noorman, Nur Sarah Iman; Jaafar, Ezureen Natasya Kahar; Amiruddin, Nur Adleena Natasha; Khairul Azman, Muhammad Khairul Haiqal Bin; Ramlan, Aini Faezah; Herdiansah, Ari Ganjar; Djuyandi, Yusa (Universitas Padjadjaran, 2024)
Social media sites are now vital resources for political activism and engagement. Social media sites like Facebook, Instagram, Twitter, and TikTok are essential for encouraging political engagement and awareness among users because they enable the real-time sharing of news, viewpoints, and conversations. These observations highlight the changing nature of media consumption and political participation, highlighting the increasing significance of digital platforms and user-generated material in addition to conventional news sources. This study, titled explores the significant role of social media in shaping the political engagement of Malaysian youth during the 15th General Election (GE15. Utilizing the Uses and Gratification Theory (UGT) and the Technology Acceptance Model (TAM) as theoretical frameworks, this research delves into the motivations behind social media use and the factors influencing its acceptance among young voters. By integrating these frameworks, the study seeks to understand why Malaysian youth used social media during GE15 to engage in politics. This research synthesizing data from several sources, such as the papers, reports, and public opinion on social media. This research contributes to the understanding of digital political behavior by demonstrating how social media functions as a vital tool for youth political engagement in Malaysia’s General Election (GE) 15th. It underscores the importance of considering both psychological gratifications and technological acceptance when analyzing the impact of social media on political involvement.